SISTEM PROTEKSI HUBUNG SINGKAT PADA MOTOR INDUKSI 3 FASA BERBASIS ARDUINO - Khoiriah Sari; Raden Rizki Alkawesar; Surojo Surojo; Yudhi Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The frequent use of three-phase induction motors in the factory continuously can cause the motor to experience disturbances. One of them is a short circuit current that causes a decrease in motor speed and increases the motor temperature. To overcome this problem, a protection system is designed that protects the motor from short-circuit currents in phase-neutral. The protection system is designed using the ACS712 30A sensor as a short-circuit current reader with a minimum reading of 2A and a maximum of 25A. When a short circuit occurs, the SSR 25DA will disconnect the source from the mains circuit. The results of the demonstration, the short-circuit current measurement values ​​are 3.20A and 2.22A with 56Ω and 68 resistance. The short-circuit current with a resistance of 1.5Ω is not read by the ACS712 sensor due to overload, therefore the short-circuit current value obtained from the calculation is 146.7A. From the demonstration, it can be concluded that the resistance on the resistor affects the short circuit current value that is read. This is justified by Ohm's Law which reads that the electric current in an electric load is directly proportional to the voltage and inversely proportional to the resistance.